THE STUDENTS’ PROBLEMS IN LISTENING COMPREHENSION - Maulidiyah, Noor (LET: Linguistics, Literature and English Teaching Journal, 2015)
The research aims to investigate the students? problems in listening comprehension.  The research has two statements of problems: (1) How do the fifth semester students perceive the importance of studying listening comprehension at the English Department of Tarbiyah and Teachers Training Faculty at Antasari State Institute for Islamic Studies Banjarmasin in the academic year of 2013/2014? And (2) What problems do the fifth semester students encounter the most in listening comprehension at the English Department of Tarbiyah and Teachers Training Faculty at Antasari State Institute for Islamic Studies Banjarmasin in the academic year of 2013/2014?